Building Public Order through Siyasah Dusturiyah: The Role of Government in Preventing Illegal Street Racing - Rahmadini, Rahmadini; Nurhikma, Nurhikma; Utamy, Hebby Rahmatul; Putri, Dewi (JISRAH: Jurnal Integrasi Ilmu Syariah, 2024)
Abstract: The main issue discussed in this thesis is the ongoing occurrence of illegal racing in Bukittinggi, which contradicts the Bukittinggi Regional Regulation No. 3 of 2015 on Public Order and Tranquility, specifically Article 10, letter a, which prohibits any individual from engaging in racing, speeding, or standing on the road without permission. The purpose of this research is to examine the form of law enforcement by the Civil Service Police Unit (Satpol PP) in addressing illegal racing in Bukittinggi and to analyze the perspective of *Siyasah Dusturiyah* on the authority of Satpol PP in enforcing Bukittinggi Regional Regulation No. 3 of 2015. This research is field research with a descriptive qualitative approach. Primary data sources include Civil Servant Investigators (PPNS) from the Bukittinggi Satpol PP and individuals involved in illegal racing activities. Secondary data sources include the local community around the illegal racing locations. The findings of this study show that Satpol PP’s efforts to combat illegal racing in Bukittinggi are in two forms. First, the pre-emptive law enforcement focuses on prevention through education and outreach activities conducted directly to the public and through media. Second, preventive law enforcement is aimed at preventing legal violations or criminal acts before they occur, such as conducting routine patrols in areas prone to illegal racing and collaborating with related institutions like the Police and the Department of Transportation. Viewed from the Siyasah Dusturiyah perspective, the authority of Satpol PP is relevant to the concept of Wilayatul Hisbah and Ulil Amri. Wilayatul Hisbah emphasizes the task of supervision and enforcement of goodness (amar ma'ruf) and the prevention of wrongdoing (nahi munkar). The enforcement of illegal racing regulations is a form of nahi munkar carried out by Satpol PP to ensure that public behavior remains within safe and lawful boundaries. This action by Satpol PP is in line with the principle of Ulil Amri, which stresses the importance of legitimate authority in maintaining public welfare and safety.